2012
DOI: 10.1007/s00421-012-2412-y
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric exercise inhibits the H reflex in the middle part of the trapezius muscle

Abstract: The objectives of this study were to (1) investigate the modulation of the H reflex immediately after and 24 h after eccentric exercise in the presence of delayed-onset muscle soreness (DOMS) and (2) test the reproducibility of the H reflex in trapezius across days. H reflexes were recorded from the dominant middle trapezius muscle by electrical stimulation of the C3/4 cervical nerve in ten healthy subjects. DOMS was induced by eccentric exercise of the dominant shoulder. H reflexes were obtained in four sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 40 publications
9
37
0
Order By: Relevance
“…For instance, the pain intensity reported 24 hours after ECC has both been shown to increase and to remain constant. 18,24 In the present study, we found increased soreness intensity and soreness area at 24 hours after compared with before ECC in line with one of our previous studies. 8 Concerning the changes in maximal force, both decreased and unchanged maximal strengths during shoulder elevation have been reported.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For instance, the pain intensity reported 24 hours after ECC has both been shown to increase and to remain constant. 18,24 In the present study, we found increased soreness intensity and soreness area at 24 hours after compared with before ECC in line with one of our previous studies. 8 Concerning the changes in maximal force, both decreased and unchanged maximal strengths during shoulder elevation have been reported.…”
Section: Discussionsupporting
confidence: 93%
“…Even for this muscle, the extent of changes in the assessed indirect biomarkers has been reported to fluctuate due to between‐subject variations in response to the same ECC protocol. For instance, the pain intensity reported 24 hours after ECC has both been shown to increase and to remain constant . In the present study, we found increased soreness intensity and soreness area at 24 hours after compared with before ECC in line with one of our previous studies .…”
Section: Discussionsupporting
confidence: 93%
“…For the current findings, changes in excitability of spinal motoneurons cannot be ruled out. Previous studies, which have reported increases, decreases, or no change in H-reflexes after a single session of various types of training, have ascribed such findings to presynaptic mechanisms (i.e., altered presynaptic inhibition or homosynaptic postactivation depression of Ia afferents), rather than altered motoneuron excitability (17,22,34). Such processes, which change the level of facilitation from muscle spindle input to the motoneurons, are unlikely to influence the CMEP measured in a relaxed muscle, as in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…; Nottle and Nosaka ) that could have then affected walking and/or H‐reflexes on the other 2 days of testing (Vangsgaard et al. ). None of our participants had ever engaged in uninterrupted Ds treadmill walking as used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Upslope and Lv walking were randomized to days 1 and 2. Downslope walking was always reserved for day 3 because of the potential for delayed onset muscle soreness (Whitehead et al 2001;Farr et al 2002;Nottle and Nosaka 2005) that could have then affected walking and/ or H-reflexes on the other 2 days of testing (Vangsgaard et al 2013). None of our participants had ever engaged in uninterrupted Ds treadmill walking as used in this study.…”
Section: Methodsmentioning
confidence: 99%